The Role of Brand Image in Mediating the Impact of Word of Mouth on Purchasing Decisions - Nurul Qomariah; Devi Rosdiana Maharani; Arik Susbiyani; Ni Nyoman Putu Martini (www.amertainstitute.com, 2024)
Purchasing decision is an important stage in consumer behavior that has broad implications, both locally and globally. Thus, it is important to discuss the issue of purchasing decisions made by consumers. This paper aims to determine the effect of word of mouth on purchasing decisions with brand image as a moderation at PT XYZ. The population in this study were all consumers of PT XYZ, a company engaged in the production of snacks in Malang Regency. The number of samples was determined as many as 100 respondents. Validity tests and reliability tests were carried out in this study so that the measuring instrument used truly met the rules of a measuring instrument. Hypothesis testing was also carried out in this study so that the impact of the independent variables on the dependent variables could be clearly identified. The results of the study showed that word of mouth had a positive and significant effect on purchasing decisions. Brand image had a positive and significant effect on purchasing decisions. Word of mouth had a positive and significant effect on brand image. Word of mouth had a positive and significant effect on purchasing decisions through brand image.